Estudo das propriedades de argamassas com uso de vermiculita expandida como substituto parcial da areia natural - Xavier, Moizes de Souza (Universidade Federal Rural do Semi-Árido, 2018)
With the increase of available technologies and the need to adapt to norms that aim at the performance of buildings, the study of new materials that can add characteristics not available in conventional mortars is of paramount importance, mainly in terms of energy efficiency and thermal comfort. In this perspective, the present work proposes to investigate the thermal insulation characteristics in cement slabs, which simulate the coating, with proportions of replacement of natural sand by expanded vermiculite defined in 0%, 25%, 50% and 75%. Fresh properties were also analyzed as density and consistency, and in the hardened state as tensile strength in bending, compressive strength and capillary absorption in each of the traces. To analyze the thermal performance of each trace, cement plates of each substitution content were produced. The results show that the mortar with 75% expanded vermiculite had the best thermal behavior, and the trait with the best thermomechanical properties was replaced with 50% of the light aggregate, presenting mechanical strength values higher than that of mortar with content of 0%.
Monografia
Keywords: Desempenho térmico; Eficiência energética; Propriedades termomecânicas; Agregado leve; Thermal performance; Energy efficiency; Thermomechanical properties; Lightweight aggregate; ENGENHARIAS::ENGENHARIA CIVIL